Balancing against China with the Asia-Africa growth corridor: an Indian-Japanese initiative towards the Indo-Pacific - Nicolini Gabriel, João Paulo (2018)
This paper aims to analyse whether the Indian-Japanese initiative Asia-Africa Growth Corridor (AAGC) can be considered a strategy to curb China's supposed capacity of diplomatically isolating its regional rivals while attempting to consolidate the Indo-Pacific as an area of influence. The hypothesis is that, in a moment of uncertainty over United States’ commitment with their Asian traditional partners and allies, India and Japan are encouraged to develop new mechanisms to balance against China. According to the Realist school of International Relations, India and Japan will virtually seek manners to balance against China in order to defend their interests. This paper develops the argument using the concepts of ‘balancing of threat’ and ‘soft balancing’ to describe the strategies developed by these countries within the Indo-Pacific.